Development of a Tool to Assess Basic Competency in the Performance of Rigid Bronchoscopy - Mahmood, Kamran; Wahidi, Momen M.; Osann, Kathryn E.; Coles, Kathleen; Shofer, Scott L.; Volker, Ellen E.; Davoudi, Mohsen (Annals of the American Thoracic Society, 2016)
Rigid bronchoscopy is increasingly used by pulmonologists for the management of central airway disorders. However, an assessment tool to evaluate the competency of operators in the performance of this technique has not been developed. We created the Rigid Bronchoscopy Tool for Assessment of Skills and Competence (RIGID-TASC) to serve as an objective, competency-oriented assessment tool of basic rigid bronchoscopic skills, including rigid bronchoscopic intubation and central airway navigation. To assess whether RIGID-TASC scores accurately distinguish the basic rigid bronchoscopy skills of novice, intermediate, and expert operators, and to determine whether RIGID-TASC has adequate interrater reliability when used by different independent testers. At two academic medical centers in the United States, 30 physician volunteers were selected in three categories: 10 novices at rigid bronchoscopy (performed at least 50 flexible, but no rigid, bronchoscopies), 10 operators with intermediate experience (performed 5-20 rigid bronchoscopies), and 10 experts (performed ≥100 rigid bronchoscopies). Participants included pulmonary and critical care fellows, interventional pulmonology fellows, and faculty interventional pulmonologists. Each subject then performed rigid bronchoscopic intubation and navigation on a manikin, while being scored independently by two testers, using RIGID-TASC. Mean scores for three categories (novice, intermediate, and expert) were 58.10 (±4.6 [SE]), 78.15 (±3.8), and 94.40 (±1.1), respectively. There was significant difference between novice and intermediate (20.05, 95% confidence interval [CI] = 7.77-32.33, P = 0.001), and intermediate and expert (16.25, 95% CI = 3.97-28.53, P = 0.008) operators. The interrater reliability (intraclass correlation coefficient) between the two testers was high (r = 0.95, 95% CI = 0.90-0.98). RIGID-TASC showed evidence of construct validity and interrater reliability in this setting and group of subjects. It can be used to reliably and objectively score and classify operators from novice to expert in basic rigid bronchoscopic intubation and navigation.